(untitled) (Acta Scientiarum. Animal Sciences, 2025)
The objective of this research is to evaluate the physiological variables altogether and determine which variables have the greatest power to explain the data variation in terms of adaptive profile, using canonical and stepwise discriminant analysis. Eighteen non-castrated male sheep of the Soinga, Morada Nova, and Santa Inês breeds were used, with an average age of 5±1.0 months and an average weight of 15 ± 2.3 Kg. The RT showed a significant correlation above 50% with the temperature of the scrotum and leg; RR showed a higher correlation with tympanic (69%) than with RT (53%) tympanic showed a correlation above 70% with the temperature of the chest, back, buttocks, testicles, and leg, and 63% with the temperature of the eye, while RT showed a correlation of less than 50% with the temperature of the chest, buttocks, back and eye, and 51% with the testicle and leg. The most discriminatory variables for native breeds at comfort temperatures and thermal stress were reat rate and tympanic temperature. Tympanic temperature proved to be an important physiological variable to aid in the study of the adaptive profile of animals.